Towards an "Algorithm Constitutional by Design" (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
We focus on the Internet constitutional rules linked with the algorithmic decision-making. The reasoning is structured upon two related topics. Firstly, the regulatory model well tailored to the Internet: hard or soft law. Secondly, the constitutional legitimacy arising from each model: at the national and European levels. The algorithms are assumed as test for the resistance or not of the binomial category: fundamental rights/public power. They pose the challenge to design new reasonable paradigms able to take into account the visibility and the intelligibility of algorithms. The Author leaves us with a basic question: a rule suited to draw an "algorithm Constitutional by design".
Keywords: Internet; algorithm; Constitution; European Union; regulation